Cesium tungsten bronze nanostructures and their highly enhanced hydrogen gas sensing properties at room temperature. (21st July 2021) - Shrisha,; Wu, Chang-Mou; Motora, Kebena Gebeyehu; Kuo, Dong-Hau; Lai, Chiu-Chun; Huang, Bohr-Ran; Saravanan, Adhimoorthy
Abstract: In this study, cesium tungsten bronze (Csx WO3 ) a well-known metal oxide semiconductor and excellent photocatalyst and active photothermal material was used as a sensing material toward hydrogen for the first time. The Csx WO3 nanorods were synthesized using a new hydrothermal method and examined through systematic material investigations. The synthesized Csx WO3 nanorods were coated on SiO2 /Si substrates and subsequently fabricated laterally with multi-finger platinum (Pt)-based electrodes to test their gas detecting properties. The gas detecting property of the prepared material was studied toward very toxic hydrogen gas (10–500 ppm concentration). The gas sensing results demonstrate that the synthesized Csx WO3 material has excellent gas sensing properties toward hydrogen (31.3%), which is overwhelmingly superior to as-prepared WO3 (4.7%) due to its suitable electrical and optical properties at room temperature (RT). The selectivity results also indicate that the material has outstanding selectivity toward hydrogen compared with different gases such as ammonia and carbon dioxide. The critical features of this material are its high reliability, simple synthesis method, low humidity susceptibility, and high selectivity, making it viable for use in hydrogen sensors. Compared with the as-prepared WO3, the adsorption capability and conductance of the Csx WO3 surface induces active O2 functional groups, significantly enhancing the gas sensing properties. Highlights: Cesium tungsten bronze nanostructures H2 gas sensor was prepared by solvothermal. It showed excellent H2 gas sensing ability and selectivity. The sensing property of the developed sensor was less affected by humidity.